2014
DOI: 10.1007/s11259-014-9590-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of Duddingtonia flagrans and Monacrosporium thaumasium in the biological control of gastrointestinal nematodes in female bovines bred in the semiarid region

Abstract: Brazil has a herd of 212 million cattle and 171 million hectares of pastures that produce approximately 96 % of Brazilian beef. The Brazilian production system enables animal infection by endoparasites, which are considered one of the main obstacles for the development of this industry and are responsible for considerable economic losses. The control of parasitic diseases is performed via the administration of antiparasitic drugs, but they leave residues of the products in the treated animal, affect non-target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…They observed that statistical differences in EPG counts (p < 0.05) only started at the 60 th day of the experiment, with a fecal egg count reduction on day 180 that was similar to what was seen in the present study (76% in adults and 83% in juveniles). Other studies have also demonstrated the ability of D. flagrans to survive after passage through the gastrointestinal tract of animals, making it a strong ally in combating free-living stages of the gastrointestinal nematodes (WALLER, 2006;PAZ-SILVA et al, 2011;SAGÜÉS et al, 2011;FITZ-ARANDA et al, 2015;ARIAS et al, 2013;SILVA et al, 2014). Strategic use of chemical treatment aided in this, by enabling accelerated reduction of the parasite load in the animals.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that statistical differences in EPG counts (p < 0.05) only started at the 60 th day of the experiment, with a fecal egg count reduction on day 180 that was similar to what was seen in the present study (76% in adults and 83% in juveniles). Other studies have also demonstrated the ability of D. flagrans to survive after passage through the gastrointestinal tract of animals, making it a strong ally in combating free-living stages of the gastrointestinal nematodes (WALLER, 2006;PAZ-SILVA et al, 2011;SAGÜÉS et al, 2011;FITZ-ARANDA et al, 2015;ARIAS et al, 2013;SILVA et al, 2014). Strategic use of chemical treatment aided in this, by enabling accelerated reduction of the parasite load in the animals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, strategies for the control of nematodes are being explored, including the use of natural nematode antagonists, i.e., nematophagous fungi. These microorganisms are being considered as suitable tools for the control and prevention of nematodias of cattle and sheep (SILVA et al, 2014). Nematophagous fungi are microorganisms from soil that can form trapping devices from their mycelia to catch, destroy and feed of nematodes in nature (LIU et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Once these spores are expelled to the soil through the animal deposition's, they germinate in situ and develop trapping devices that capture nematode larvae recently hatched from nematode eggs and eventually feed on them (MENDOZA-de-GIVES & TORRES-ACOSTA, 2012). Recent studies have demonstrated that the use of sodium alginate pellets as a vehicle for D. flagrans and Monacrosporium thaumasium (Helotiales, Orbiliaceae) can be considered a suitable tool for the control of cattle parasites (SILVA et al, 2014). Arthrobotrys species (Helotiales, Orbiliaceae) are probably the most extensively studied nematophagous fungi worldwide.…”
Section: Introductionmentioning
confidence: 99%